Composite actions within steel-FRP composite beam systems with novel blind bolt shear connections. (1st May 2017) - Satasivam, Sindu; Feng, Peng; Bai, Yu; Caprani, Colin
Highlights: Experimental investigation into the shear stiffness of blind bolt shear connectors. Failure of steel-FRP joints dependent on slab configuration and number of bolt rows. Bending stiffness of composite beam systems with two levels of composite action. Design formulation proposed, showed good agreement with experimental results. Abstract: The shear stiffness of novel blind bolts was experimentally investigated for shear connections within steel-FRP composite beam systems using steel-FRP joints loaded in tension. The number of bolt rows (either one or two bolt rows) and the effect of the pultrusion orientation of the FRP web-flange sandwich slab on joint stiffness and joint capacity were examined. It was found that joint capacity and failure modes were dependent on the pultrusion configuration of the FRP slab and the number of bolt rows. A unidirectional configuration consisting of an FRP slab with box-profiles parallel to flat panels exhibited shear-out failure, whereas a bidirectional orientation consisting of an FRP slab with box-profiles perpendicular to flat panels exhibited both shear-out and net-tension failure in the FRP component. The experimentally derived shear connector stiffness was then used in a proposed design formulation to predict the bending stiffness of modular steel-FRP composite beam systems, considering two kinds of partial composite actions. These were the composite action provided by the blind bolt shear connector and the composite action provided by transversely-oriented webs within the slab. Good agreement was observed between the experimental results and the proposed design formulation.